Assessment of Serum Lipid and Uric Acid Levels in Women with Normal Pregnancy and Pre-Eclampsia - Ghaffar, Beenish; Memon, Shahida Hassan; Khidri, Feriha Fatima (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVES: To determine and compare the serum lipid profile and uric acid concentration in pre-eclamptic and normal pregnant women. METHODOLOGY: This cross sectional study was carried out at Biochemistry Department, LUMHS Jamshoro with the collaboration of Gynaecology and Obstetrics Department and Diagnostic & Research Laboratory, Pathology Department, LUMHS Jamshoro from March 2016 to December 2016. Patients were selected via non-probability consecutive sampling. A total of 60 subjects were enrolled and divided into two groups comprising women with normal pregnancy(n=30) as controls and women with pre-eclampsia (n=30) as cases after applying exclusion criteria. RESULTS: Mean age of women with pre-eclampsia and normal pregnancy was found to be 26.77±2.58 and 26.30±2.05 years (p-value=0.44). Significantly higher levels (p-value < 0.05) of triglycerides (TG), total cholesterol (TC), low density lipoproteins (LDL) and serum uric acid were found in the women with pre-eclampsia as compared to controls; whereas, high density lipoproteins (HDL) were significantly lowered (p-value < 0.05) in women with pre-eclampsia. Uni-variate analysis showed that the TG (OR=7.67), TC (OR=3 and 5.55), LDL (OR=3.59) and uric acid (OR=11.23) were significantly increased and HDL (OR= 9.75) were significantly lowered in women with pre-eclampsia than in women with normal pregnancy (p-value < 0.05). In the multi-variate logistic model, TG (OR=4.28) and uric acid (OR=6.62) were significantly increased and HDL (OR= 4.31)were significantly lowered in women with pre-eclampsia than in women with normal pregnancy (p-value<0.05) CONCLUSION: Alteration in the serum uric acid and TG concentration may be helpful in early detection and monitoring of pre-eclampsia cases. This information may be utilized in preventing the adverse outcomes occurring as a result of pre-eclampsia.